Pautas para el estudio de los orígenes de la música cinematográfica - Alcalde de Isla, Jesús (Área Abierta. Revista de comunicación audiovisual y publicitaria, 2007)
In the origins of cinematografic music there is two fundamentals aspects with references from the postromanticisme period of music: the programatic music and the leitmotiv. In the first case the revaluation of instrumental music and the extramusical motivation give rise to a type of related music that it looks for to transmit of independent way contained with those of Literature and the other arts. In the case of leitmotiv, the repetitive character and associate, own of leitmotiv wagneriano, musically suppose an alternative to the closed forms classic and narratively a resource that facilitates the representation, reason why easily it prevailed in the musical rhetoric of the cinema. It has, nevertheless, substantial difference between leitmotiv wagneriano and the filmic one.
Keywords: Cinematographic music; Programatic music; Leitmotiv